TINGKAT KEPATUHAN PEMILIK SARANA APOTIK DALAM MELAKSANAKAN KEBIJAKAN PEMERINTAH TERHADAP PERSYARATAN PENGELOLAAN APOTIK DI KABUPATEN SRAGEN - VETYLIANASARI, AGRESTHA (Dinamika Hukum, 2015)
The purpose of this study is to assess analyze the factors that affect the level of compliance means of pharmacies in implementing policies to the requirements of pharmacy management This research uses juridical sociological study because it describes and gain clarity about government policy towards the management of the pharmacy. The nature of this research is descriptive analysis namely: